VULNERABILITY OF SMALL-SCALE FARMERS IN RELATION TO CLIMATE CHANGE AND THEIR COPING STRATEGIES: CASE STUDY OF SOUTHERN PUNJAB, PAKISTAN - M. Luqman; M. U. Mehmmod; S. Ashraf; M. Yaseen; I. Ashraf (Journal of Animal and Plant Sciences, 2021)
We examined the vulnerability of farmers to climate change in this study. This study was quantitative followed by cross-sectional research design. The study was confined to two districts of the southern Punjab: Muzaffargarh and Khanewal. A total of Two hundred and forty (240) farmers were interviewed face to face. Data were analyzed through Statistical Package for Social Sciences (SPSS). The results were categorized into three section. First section consists of socio-economic profile of respondents. The descriptive analysis was adopted in order to quantify the age, education, land size, income and income sources of the respondents. Second section entailed perception of respondents about the climate change, farmers vulnerability level, factors behind the vulnerability and coping strategies as adopted by the farmers. The mean values and standard deviation were calculated to meet the need of second objective. The third section was the Factor Analysis of the factors through Principal Component Analysis (PCA). The objective was to extract those factors likely to contribute more to vulnerability of farmers to climate change. The values of Kaser-Meyer-Olkin and Barlett’s test of sphericity were greater than 0.60, thus running factors analysis was implicit. Four factors (i) low crop yield (ii) small/subsistence farming (iii) large dependent in agriculture and (iv) marketing problem was extracted indicating total variance of 59.67%. The normality test for the newly extracted factors had the probability value of less than 0.005. At the end, the study had brief recommendations for the research, extension and the farmers in order to improve the adaptive capacities of the farmers and persuade climate smart agriculture.
Keywords: Adaptation; Coping strategies; Climate change; Small farmers